Unveiling the Neglected Rights: Miranda Rule Advocacy for Impoverished Defendants in Indonesian Criminal Cases under Law No. 16 of 2011 - Pratama, Wahyu Rizki; Haryo, Michael (Universitas Negeri Semarang, 2022)
This paper examines the application and impact of the Miranda Rule in the Indonesian legal system, particularly concerning impoverished defendants, within the framework of Law No. 16 of 2011. Originating from investigator negligence during the interrogation of an Arizona citizen, the Miranda Rule has evolved into a crucial legal principle safeguarding the rights of suspects as citizens, with constitutional implications. The study investigates the incorporation of Miranda principles into Indonesian legislation, focusing on its relevance to providing legal aid for impoverished individuals accused of criminal acts. The research traces the historical trajectory of the Miranda Rule, emphasizing its transformative role in shaping legal norms and protecting individual rights. It analyzes the specific provisions within Law No. 16 of 2011 that address the needs of impoverished defendants and explores the practical implications of these provisions in real-world legal scenarios. Furthermore, the paper sheds light on the broader consequences of the Miranda Rule, examining its influence on derivative regulations that redefine the legal status of individuals within the Indonesian legal framework. The advocacy for impoverished defendants is a central theme, emphasizing the rule's role in ensuring justice and welfare for all citizens. Through a comprehensive analysis of legal texts, case studies, and practical implications, this paper contributes to the understanding of how the Miranda Rule, as enshrined in Law No. 16 of 2011, intersects with the rights and well-being of impoverished defendants within the Indonesian criminal justice system.